Comparison of the Nutritional Composition of Meat Products Derived from Croatian Indigenous Pig Breeds - Ana Vulić; Željko Cvetnić; Ivica Kos; Ivan Vnučec; Nada Vahčić; Tina Lešić; Dimitrije Simonović; Nina Kudumija; Jelka Pleadin (Foods)
There is a growing interest in the preservation of indigenous pig breeds, as they serve as a valuable genetic reserve. Pork meat products are widely consumed due to their desirable flavor, which is largely influenced by their chemical composition and the production processes employed. The aim of this study was to characterize and compare the nutritional composition, mineral content, and fatty acid profile of meat products derived from indigenous Croatian pig breeds. Three types of meat products, including bacon, dry-cured ham, and dry-fermented sausages, originating from the Turopolje pig, Black Slavonian pig, and Banijska šara, were collected and analyzed for proximate composition, fatty acid profile, and mineral content. Concerning the proximate analysis, statistically significant differences were found in the water and fat content in bacon and dry-fermented sausages, while the mineral analysis revealed differences in iron content. The fatty acid profile of the tested products was found to be in accordance with previously reported data. The results indicated similarities in chemical composition, mineral content, and fatty acid profile between meat products from different pig breeds; however, performing PCA analysis revealed that the major influence on product and breed characterization could be attributed to differences in fatty acid composition.